Aspek Finansial Dan Aspek Kepemilikan Dalam Kinerja Keuangan Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia - Natasia Alinsari; Lina Devita Putri (Jurnal Akademi Akuntansi, 2022)
This research aims to explain the influence of financial aspects such as liquidity, firm size, working capital, sales growth, and ownership aspects such as managerial ownership, institutional ownership, government ownership, foreign ownership, family ownership, on financial performance. The sample of this research is 54 companies that are members of the basic and chemical industries listed on the IDX for the 2016-2020 period with a total of 270 observations. Hypothesis testing is carried out by multiple regression analysis. The research results reveal that government ownership has a negative impact on profitability, while institutional ownership, sales growth, and foreign ownership have a positive impact on company profitability. However, for the variables of family ownership, firm size, managerial ownership, and working capital have no impact on profitability. The results of this research can be used as a reference for investors in determining the company to invest in. Investors should invest their capital in companies with institutional ownership or foreign ownership because they have adequate potential, both in terms of funding potential or human resource potential, as well as other supporting potentials.